Uso das tecnologias no ensino da disciplina de libras nas escolas da rede municipal de Porto Nacional -TO - Ribeiro, Lucélia dos Santos (Universidade Federal do Tocantins, 2022)
This article shows the Laws related to the Brazilian Sign Language - Libras in Brazil and its importance for the deaf community. It is the importance of inserting the Letras-Libras course at the Federal University of Tocantins UFT campus of Porto Nacional, through the course the Libras discipline was inserted in the municipal curriculum, a survey was made with the teachers who teach the Libras discipline and people who were responsible for the insertion of this discipline. After the research, it was possible to perceive the importance of the Libras subject inserted in the curriculum of the municipality of Porto National-TO and the importance of technology at this moment in the teaching-learning process of students.